Influência das capacidades dinâmicas no desenvolvimento de inovações orientadas à sustentabilidade em organizações que atuam em clusters: proposta e análise de um framework - Silva, Jean Soares da (2021)
Sustainability-Oriented Innovation (SOIs) is a theme that is increasingly prominent in academic, corporate, and governmental discussions. In this context, capabilities, especially dynamic capabilities (DCs), contribute to developing innovation activities, mostly when organizations operate in collaborative environments that involve different actors. Recently, the literature has focused on DCs and their importance for the development of sustainabilityoriented innovation. However, much of the research focuses on specific dynamic capabilities, innovation activities from the triple bottom line's perspective, organizations that work in isolation (without strong inter-organizational relationships), or organizations operating in supply chain collaboration networks. Thus, through dynamic capability view and activities for SOIs (from the perspective of operational optimization, organizational transformation, and systems construction proposed by Adams et al., 2016), we propose a framework that relates the influence of dynamic capabilities in the development of innovation activities oriented to sustainability organizations that operate in clusters. The literature analysis identified eight dynamic capabilities (and eleven facilitators associated with these CDs) that influence innovation activities oriented to sustainability. A conceptual framework has been proposed that relates these dynamic capabilities (and their facilitators) to SOI activities from operational optimization, organizational transformation, and systems building. The framework was applied and refined through case studies in four organizations in different clusters. Data collection took place through semi-structured interviews and documents referring to the organization's activities and its clusters. The collected data were analyzed using the content analysis technique, using the Atlas.ti software, which made it possible to organize and categorize the data collected in the research. From the empirical evidence, it was possible to verify which CDs (and facilitators) influence SOI activities in the context of the organizations studied and how this influence relationship occurs. The empirical evidence allowed the elaboration of 15 research propositions. As contributions, we highlight the development and refinement of the framework; the propositions that emerged from empirical research; and the advancement of literature on the subject since we studied different constructs in an integrated manner.